Analysis of Digital Financial Literacy Factors of Students at SMA Negeri 4 Jakarta - Renova Sitorus; Suparno; Ari Saptono (Yayasan Sinergi Kawula Muda, 2026)
This study aims to analyze the influence of financial knowledge (FK), financial behavior (FB), and digital skills (DS) on digital financial literacy (DFL) among high school students at SMA Negeri 4 Jakarta. Using a quantitative approach with a cross-sectional survey, the study tested four hypotheses through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed that financial knowledge significantly affects digital financial literacy directly and has an indirect impact through digital skills. However, financial behavior did not have a statistically significant effect on students’ digital financial literacy. Digital skills were found to have a significant positive effect on digital financial literacy. The study emphasizes the importance of digital skills in enhancing financial literacy within the context of the digital economy. This study offers a novel empirical contribution by proposing a digital financial literacy model for high school students in Indonesia that highlights digital skills as a key mechanism while revealing the limited role of financial behavior at this educational level.